Local means denoising of ECG signal. (August 2019) - Qian, Chunqiang; Su, Honghong; Yu, Helong
Highlights: A simple method to estimate standard deviation of additive white Gaussian noise in the ECG signal was presented. Local Means (LM) method which is a "local" version of the NLM method is introduced. LM method has about 2 order of magnitude lower computational cost than NLM method. In a low SNR level condition, the signal-to-noise (SNR) improvement increases via LM method, by 21% compared to NLM method. Abstract: Electrocardiograph (ECG) signals denoising by Non-Local Means (NLM) method can achieve high signal-to-noise ratio improvements with less waveform distortion. But, computational complexity constraints its potential application in ECG signal real-time denoising. In this paper, firstly we present a simple method to determine standard deviation of additive white Gaussian noise in the ECG signal. Then, a fast ECG signal denoising method, Local Means (LM) method, which is a "local" version of the NLM method is introduced. LM method has about 2 order of magnitude lower computational cost than NLM method due to the "local search." In a low SNR level condition, the signal-to-noise (SNR) improvement increases via LM method, by 21% compared to NLM method.